FECTO DE LA SALINIDAD EN LA SUPERVIVENCIA Y CRECIMIENTO DE CRÍAS DE CABALLITO DE MAR HIPPOCAMPUS REIDI GINSBURG EN CAUTIVERIO (Boletín de Investigaciones Marinas y Costeras, 2016)
This study was conducted to determine the optimal salinity for the culture of H. reidi fry during the fist month of life, evaluating the effect of different salinities (27, 30, 33, and 36) on its growth and survival. The fry were distributed at three ind.L-1 density in 12 L incubators, animals were fed ad libitum throughout the experiment, survival was monitored daily, and height and weight were measured both at the beginning and end of the experiment. The salinity did not show signifiant differences between treatments, the highest survival rate was obtained at 27 with 17.59 ± 6.99%.